2018
DOI: 10.1007/s40519-018-0517-y
|View full text |Cite
|
Sign up to set email alerts
|

Orthorexia nervosa in a sample of Portuguese fitness participants

Abstract: Level V: Descriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 34 publications
10
60
2
7
Order By: Relevance
“…Our results corroborate earlier findings of Eriksson et al (2008), who reported that ON behaviors increased with the increase of self-reported exercise frequency, but only in female fitness participants [24]. The relationship between time spent on exercise and the ON symptoms rate was also confirmed by other studies conducted in the student's population [5,25], among athletes [13,21] and gym attendees [4,6].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results corroborate earlier findings of Eriksson et al (2008), who reported that ON behaviors increased with the increase of self-reported exercise frequency, but only in female fitness participants [24]. The relationship between time spent on exercise and the ON symptoms rate was also confirmed by other studies conducted in the student's population [5,25], among athletes [13,21] and gym attendees [4,6].…”
Section: Discussionsupporting
confidence: 92%
“…Some studies suggest that there is a link between ON and exercise habits [4][5][6][7]. Involvement in sport, particularly at the elite level, creates many nutritional challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Vorweg sei gestellt, dass sich bisher noch kein Instrument zur Diagnosestellung und Erfassung der ON durchgesetzt hat. In Anlehnung an den Bratman Orthorexia Test (10 Fragen) [12] entwickelte eine italienische Arbeitsgruppe den 15 Fragen umfassenden ORTO-15 [19], für den mittlerweile auch Übersetzungen in die englische [20,21], portugiesische [22], spanische [23], türkische [24][25][26][27][28][29], ungarische [30], polnische [31][32][33] sowie deutsche Sprache [34] vorliegen. Der Literaturüberblick deutet an, dass vor allem Personenkreise mit einem ausgeprägten Gesundheitsbewusstsein und Ernährungswissen (Diätassistenten, Studierende der Ernährungswissenschaften und Sportwissenschaften, Medizinstudierende und Ärzte, Yoga-Praktiker) betroffen scheinen.…”
Section: Diagnostik Und Prävalenzunclassified
“…Some recent studies have suggested that there is a link between ON and exercise habits both in students and the general population [ 20 – 22 ]. One of the studies in a student population found that orthorexic eating habits were associated with high exercise volumes suggesting students who play sports and, therefore, exercise more frequently, might display higher ON symptoms [ 21 ].…”
Section: Introductionmentioning
confidence: 99%